Implementation of Land Certificate Registration Procedures which the Mechanism is Not in Accordance with the General Principles of Good Government: Implementation of Land Certificate Registration Procedures which the Mechanism is Not in Accordance with the General Principles of Good Government - Alfrida Rahmadhani Anita Putri; Hendry Julian Noor (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
This research aims to analyze the implementation of Standard Operating Procedures (SOP) for land certificates registration whose mechanisms are not in accordance with the General Principles of Good Government (AUPB) based on Decision Number 12/G/2019/PTUN.JBI and improvements and changes to the land office for the future regarding the land certificate registration process whose mechanism is in accordance with AUPB. This is normative legal research using a statutory regulation approach and a case approach. The results of this research are the field review stage until the issuance of a certificate of violation of the SOP based on PP 24/1997 and Minister of ATR/KBPN Regulation Number 12 of 2021. The Head of the Jambi City Land Office violated the AUPB, namely the principles of accuracy, legal certainty, fair play, and mixing up authority. Improvements to the land office are that all BPN services will be switched electronically, including electronic certificates for the public carried out in stages. The Touch My Land application overcomes administrative weaknesses. STPN produces skilled measuring officers. PTSL maps village land to minimize overlap. The land certificate registration mechanism must be guided by land regulations and AUPB. Keywords: Standard Operating Procedures; Land Certificate Registration; General Principles of Good Government; Land Office.